Technology, Science and Culture A Global Vision, Volume IV - Ricardo Hernández, Luis; Alejandro Serrano Meneses, Martín (IntechOpen, 2023)
Following the success of the first, second and third volumes of this series, we are keen to continue our discussions on research topics related to the fields of food science, intelligent systems, molecular biomedicine, water science, and creation and theories of culture. Our aims are to discuss the latest topics, theories, and research methods in each of these fields, to promote debate among top researchers and graduate students and, in the process, to generate collaborative work.